Resource distribution and the trade‐off between seed number and seed weight: a comparison across crop species - Gambin, Brenda Laura (2009)
In grain crops, total sink capacity is usually analysed in terms of two components, seed number and individual seed weight. Seed number and potential individual seed weight are established at a similar timing, around the flowering period, and seed weight at maturity is highly correlated with the potential established earlier. It is known that, within a species, available resources during the seed set period are distributed between both yield components, resulting in a trade-off between seed number and seed weight. Here we tested if this concept could apply for interspecific comparisons, where combinations of numbers and size across species could be related to the total available resources being either allocated to more seed or larger potential individual seed weight during the seed set period. Based on this, species differences in seed weight should be related to resource availability per seed around the period when seed number is determined. Resource availability per seed was estimated as the rate of increase in aboveground biomass per seed around the period of seed set. Data from 15 crop species differing in plant growth, seed number, seed weight and seed composition were analysed from available literature. Because species differed in seed composition, seed weight was analysed following an energy requirement approach. There was an interspecific trade-off relationship between seed number per unit of land area and seed weight (r = 0.92; F(1,13) = 32.9; n = 15; P < 0.001). Seed weight of different species was positively correlated (r = 0.90; F(1,13) = 52.9; n = 15; P < 0.001) with resource availability per seed around the seed set period. This correlation included contrasting species like quinoa (Chenopodium quinoa; ∼100 000 seeds m−2, ∼4 mg equivalent-glucose seed−1) or peanut (Arachis hypogaea; ∼800 seeds m−2, ∼1000 mg equivalent-glucose seed−1). Seed number and individual seed weight combinations across species were related and could be explained considering resource availability when plants are adjusting their seed number to the growth environment and seeds are establishing their storage capacity. Available resources around the seed set period are proportionally allocated to produce either many small seeds or few larger seeds depending on the particular species.